2017
DOI: 10.1161/jaha.117.006648
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Validation of a Geriatric‐Sensitive Perioperative Cardiac Risk Index

Abstract: BackgroundSurgical patients aged 65 and over face a higher risk of cardiac complications from noncardiac surgery. The Revised Cardiac Risk Index (RCRI) and the Gupta Myocardial Infarction or Cardiac Arrest (MICA) calculator are widely used to predict this risk, but they are not specifically designed to predict MICA in geriatric patients. Our hypothesis is that a new geriatric‐sensitive index, derived from geriatric data, will capture this population's unique response to risk factors.Methods and ResultsThe mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 23 publications
1
37
1
1
Order By: Relevance
“…From this collection, 10 articles were selected for analysis. 1,2,[15][16][17][18][19][20][21][22] Citation chaining, the process of finding studies that reference each other as described by Ellis,23 identified one additional article for inclusion ( Figure 1). 24 The 11 identified risk indices together include 2,910,297 patients, representing 17,925 cardiac events or 0.0062 events/patient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From this collection, 10 articles were selected for analysis. 1,2,[15][16][17][18][19][20][21][22] Citation chaining, the process of finding studies that reference each other as described by Ellis,23 identified one additional article for inclusion ( Figure 1). 24 The 11 identified risk indices together include 2,910,297 patients, representing 17,925 cardiac events or 0.0062 events/patient.…”
Section: Resultsmentioning
confidence: 99%
“…The area under the receiver operating characteristic curve (AUROC), a measure of the discrimination of the risk indices, 27 was very good (0.83e0.90) for the three large NSQIP studies (Davenport et al, 15 Gupta et al 2 , and Bilimoria et al 24 ), and good (0.70e0.79) for the remaining studies ( Figure 2B). Only four studies (Davenport et al, 15 Gupta et al, 2 Bilmoria et al, 24 and Alrezk et al 19 ) reported the calibration of their models, which was good in each case (Supplemental Table 2).…”
Section: Operating Characteristics Of the Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Revised Cardiac Risk Index 34 estimates postoperative cardiac events in the general population; a more recent cardiovascular risk score for elderly surgical patients had moderate accuracy 35 . The Revised Cardiac Risk Index 34 estimates postoperative cardiac events in the general population; a more recent cardiovascular risk score for elderly surgical patients had moderate accuracy 35 .…”
Section: Discussionmentioning
confidence: 99%